HUBUNGAN KEPEMIMPINAN DENGAN MOTIVASI KERJA PEGAWAI DI BAGIAN ASISTEN PEMERINTAHAN KANTOR GUBERNUR SUMATERA SELATAN - Antartila Rezki Aziz (Jurnal Ilmu Administrasi dan Studi Kebijakan (JIASK), 2020)
The purpose of this research is to see the connection between leadership and work motivation of employee at Government Assistant Office of the Governor of South Sumatra. The population are 89 and the sample are 55 which taken using Cohcran formula. The instrument of this research is question with Likert scale models that had tested for validity and reliability. Data analyzed using product moment correlation formula. The result of this research there are meaningful relationship between leadership and work motivation of employee Government Assistant Office of the Governor of South Sumatra.